2018
DOI: 10.1002/cssc.201801132
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Synthesis of Biomass‐Derived Surfactants by Reacting Hydroxymethylfurfural, Glycerol, and Fatty Alcohols on Solid Acid Catalysts

Abstract: A new type of biomass-derived non-ionic surfactants has been obtained by reacting hydroxymethylfurfural (HMF), glycerol, and fatty alcohols. For instance, 5-(octyloxymethyl)furfural glyceryl acetal can be obtained in a one-pot process by etherification of HMF with fatty alcohols followed by acetalization with glycerol. For a successful solid catalyst, acidity and polarity have to be optimized to improve conversion, selectivity, and catalyst deactivation owing to the different adsorption characteristics of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 30 publications
1
24
0
1
Order By: Relevance
“…They are shown to have good solubility and stability towards oxidation but hydrolyze in the presence of acid [4] . This class of compound and its derivatives also have shown potential in different applications including as surfactant, [5] fuel additives [6–8] and anti‐freezing agent [9,10] . Dodson et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are shown to have good solubility and stability towards oxidation but hydrolyze in the presence of acid [4] . This class of compound and its derivatives also have shown potential in different applications including as surfactant, [5] fuel additives [6–8] and anti‐freezing agent [9,10] . Dodson et al.…”
Section: Introductionmentioning
confidence: 99%
“…[3] They are shown to have good solubility and stability towards oxidation but hydrolyze in the presence of acid. [4] This class of compound and its derivatives also have shown potential in different applications including as surfactant, [5] fuel additives [6][7][8] and anti-freezing agent. [9,10] Dodson et al (2014b) showed the anti-oxidant activity exhibited by aromatic glycerol acetal indicated wide range of potential of this class of compound in industrial application including biodiesel industry.…”
Section: Introductionmentioning
confidence: 99%
“…5‐Hydroxymethylfurfural (HMF), obtained by dehydration of hexoses, constitutes one of the most important and versatile platform molecules, owing to its broad range of potential applications in the biofuels and chemical industries. Numerous transformations of HMF, such as, oxidation, reduction, etherification, alkylation, aldol condensation, acetalization, hydration, and reductive amination, have been reported in recent years . Among them, the reduction of the formyl group of HMF to afford the symmetrical diol 2,5‐bis(hydroxymethyl)furan (BHMF), has received much attention .…”
Section: Introductionmentioning
confidence: 99%
“…[120][121] The acetalization with glycerol was extended to several in situ formed 5-(alkyloxymethyl)furfurals for the preparation of potential surfactant molecules 107 and 108 in a one-pot process. [122] The resulting compounds with HLB values in the range of 4.9 to 6.6 and good thermal and water stability could be useful for industrial applications as W/O emulsifiers.…”
Section: Carbon-oxygen and Carbon-sulfur Bond Formation Reactionsmentioning
confidence: 99%